Multifarious Evolutionary Pathways of a Nuclear RNA Editing Factor: Disjunctions in Coevolution of DOT4 and Its Chloroplast Target rpoC1eU488SL. (11th February 2019) - Hein, Anke; Brenner, Sarah; Knoop, Volker
Abstract: Nuclear-encoded pentatricopeptide repeat (PPR) proteins are site-specific factors for C-to-U RNA editing in plant organelles coevolving with their targets. Losing an editing target by C-to-T conversion allows for eventual loss of its editing factor, as recently confirmed for editing factors CLB19, CRR28, and RARE1 targeting ancient chloroplast editing sites in flowering plants. Here, we report on alternative evolutionary pathways for DOT4 addressing rpoC1eU488SL, a chloroplast editing site in the RNA polymerase β′ subunit mRNA. Upon loss of rpoC1eU488SL by C-to-T conversion, DOT4 got lost multiple times independently in angiosperm evolution with intermediate states of DOT4 orthologs in various stages of degeneration. Surprisingly, we now also observe degeneration and loss of DOT4 despite retention of a C in the editing position (in Carica, Coffea, Vicia, and Spirodela ). We find that the cytidine remains unedited, proving that DOT4 was not replaced by another editing factor. Yet another pathway of DOT4 evolution is observed among the Poaceae. Although the rpoC1eU488SL edit has been lost through C-to-T conversion, DOT4 orthologs not only remain conserved but also have their array of PPRs extended by six additional repeats. Here, the loss of the ancient target has likely allowed DOT4 to adapt for a new function. We suggest rps3 antisense transcripts as previously demonstrated in barley ( Hordeum vulgare ) arising from promotor sequences newly emerging in the rpl16 intron of Poaceae as a new candidate target for the extended PPR stretch of DOT4. Altogether, DOT4 and its target show more flexible pathways for evolution than the previously explored editing factors CLB19, CRR28, and RARE1. Certain plant clades (e.g., Amaranthus, Vaccinium, Carica, the Poaceae, Fabales, and Caryophyllales) show pronounced dynamics in the evolution of editing sites and corresponding factors.